Penggunaan Media Komunikasi dalam Eksistensi Sosial Budaya Masyarakat Dayak Lawangan di Kecamatan Paku Kabupaten Barito Timur - Kristina, Della (Dharma Duta, 2024)
This study aims to analyze the use of communication media in maintaining the socio-cultural existence of the Dayak Lawangan community in Paku Subdistrict, Barito Timur Regency. Amid the rapid development of information technology, communication media serves as an essential tool for preserving cultural identity and strengthening social cohesion among indigenous communities. The research applied a qualitative approach, with data collected through interviews, observation, and documentation study. The findings reveal that the Dayak Lawangan community employs both traditional media, such as customary gatherings and ritual ceremonies, and modern media, including social media and messaging applications, to disseminate cultural values. Communication media plays a role in reinforcing community bonds, preserving language and traditions, and adapting local culture to ongoing social changes. Challenges include the influence of external cultures that may shift traditional values and limited digital literacy among the older generation. This study concludes that the use of communication media significantly contributes to preserving the socio-cultural existence of the Dayak Lawangan community and serves as a bridge between tradition and modernity.